Comparison of Sensitivity and Resistance to Ceftriaxone with Chloramphenicol in the Treatment of Salmonella typhi Infection: Literature Review - Tristianti, Imaz Zaniar; Dewi, Listiana Masyita (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
Purpose: To compare the sensitivity and resistance between ceftriaxone and chloramphenicol in the treatment of Salmonella typhi infection. Methodology: The study used a literature review method and research samples were obtained from search results using e-databases in the form of PubMed, Google Scholar, and Science Direct. Results: From the search results found 1034 articles then the researchers screened according to the inclusion and exclusion criteria, obtained 15 articles were received for review. From all studies, it was found that Salmonella typhi was more sensitive to ceftriaxone than chloramphenicol. Applications/Originality/Value: Salmonella typhi is more sensitive to ceftriaxone and more resistant to chloramphenicol.